Wage dispersion and pension funds: Financialisation of non-financial corporations in the USA, 1966-2013 - Ilhan Dögüs (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2017)
It has already been pointed out in the literature on financialisation that private pension funds have played a key role in the inflation of financial markets. This paper argues that an increase in wage dispersion between white-collar and blue-collar workers affects pension funds in a direct and structural manner. Using Saez-Zucman and fred.stlouisfed annual datasets, the proposed argument is statistically analysed by applying Vector Autoregressive modelling for the period 1966-2013 in the USA. The results show that the responses of share of pension funds within US-household wealth to one-unit shock in wage dispersion are positive and significant over the first three years. Furthermore, wage dispersion explains 11% of variations in pension funds' share in household wealth in the short-run and 19% of variations in the long-run. The study concludes that wage dispersion has a direct and structural impact on pension funds and contributes to the literature by clarifying the rise and expansion of pension funds.
Keywords: J31; D14; E44; 330; financialisation; pension funds; wage dispersion; savings out of salaries; white-collar workers; capital market inflation